Peran Pekerja Sosial dalam Meningkatkan Efektivitas Pengajaran Pendidikan Agama Di Kecamatan Percut Sei Tuan - Sani Susanti; Khodijah Tussolihin Dalimunthe; Adinda Syafira; Arum Dwi Saputri; Carissa Mumtaza Nasution; Dimas Istiqo Anggoro; Mutiara Simanungkalit (Jurnal Kemitraan Masyarakat, 2024)
This research aims to identify the problems faced by children's study groups, especially in religious education, namely Koran recitation groups. The research method used is a qualitative descriptive approach by collecting data through interviews and observations of children's study groups. The results of the research show several main problems, including children's lack of understanding about learning religion, especially reciting the Koran, for example in reading Iqro', memorizing short surahs, and also memorizing the Al-Qur'an. As a solution, the group will act as social workers, namely as Koran teachers in order to help children or children's study groups complete religious education, especially memorizing surahs and memorizing the Al-Qur'an. This research focuses on the role of a social worker, namely as a teacher in helping children's study groups increase the effectiveness of the children's study groups.